The Effect of Governance on Donations: Evidence from Brazilian Environmental Nonprofit Organizations - Adonai José Lacruz; Alexandre Reis Rosa; Marcos Paulo Valadares de Oliveira (BBR: Brazilian Business Review)
This article uses the agency theory perspective to analyze governance, composed of a set of dimensions and measured by governance factors that influence donations to Brazilian environmental Nonprofit Organizations (NPOs). Data were collected predominantly from the documents available on the Internet, and the random sample consisted of 108 observations. We identified governance dimensions through Multiple Correspondence Analysis. From these dimensions, we verified, through Partial Least Squares Structural Equation Modeling, if governance affected donations. It was observed that governance positively affected donations and that public certifications provided to NPOs in Brazil did not moderate the relationship between governance and donations. These results showing that governance helps NPOs to have easier access to the donations market and that public certifications provided to NPOs do not contribute to increasing donations. These findings are important for practitioners and also to enrich the debate about public policies for the third sector in environments of low regulation.